Immobilized Saccharomyces pastorianus Cells in Electro-fermentation: A Novel Approach to Bioethanol Production from Mustard Straw - J., Nisha; Vidya, P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The dwindling reserves of non-renewable fuels necessitate the exploration of renewable alternatives such as bioethanol. Utilizing and producing bioethanol locally boosts economies, lowers carbon footprints, and encourages self-sufficiency. One such promising lignocellulosic material that serves as an ethanol source is mustard straw. In this study, 3% sulfuric acid was used to hydrolyse fresh mustard straw, which included 4.75% moisture, 8.1% ash, 40% cellulose, 14.1% hemicellulose and 3.9% lignin, for 30 minutes at 120°C in an improvised reactor. 470-590 µg/ml of fermentable reducing sugars were produced by this procedure, as shown by glucose standardization with a UV spectrophotometer set at 540 nm. Saccharomyces pastorianus, a very effective strain of yeast that produces ethanol, has been isolated and utilized in an electro-fermentation system. In comparison to free cells, immobilizing yeast cells in calcium alginate beads provided benefits like simpler product recovery, cost-effectiveness, stability, and reusability in further fermentation procedures. The electro-fermentation process can be utilized to optimize metabolic processes taking place during fermentation and the immobilization of yeast is used to increase the ecological competence of cultures. In order to produce ethanol, the immobilized yeast cells were employed as the inoculum, with free-cell inoculum acting as the control. In comparison to free-cell cultures, immobilization led to a considerable increase in ethanol generation (15µg/ml) when external voltage of 3V was supplied. The generation of ethanol was seen decreased to14µg/ml when an external voltage of 4V was applied, in comparison to controls. These results show that modest external voltage applications can affect the ethanol production. The ethanol's identity was confirmed by the FTIR spectrum, which displayed the broad bandwidth of O-H stretch of alcohols in 3500-3200 cm-1 region, C-H bending at 2000-1650 cm-1 and carboxylic acid, C=C stretch around 1400-1395 cm-1 and 895-885 cm-1 region respectively. Thus, this work emphasizes the potential of electro-fermentation and mustard straw in the production of sustainable bioethanol.